Community-driven development and scaling-up of microfinance services: case studies from Nepal and India - Sharma, Manohar (International Food Policy Research Institute, 2004)
This case study examines the scaling-up experiences of two microfinance institutions: the Nirdhan Utthan Bank Limited (NUBL) in Nepal and the Self-Help Group (SHG)-Bank linkage program of the National Agricultural Bank for Agriculture and Rural Development (NABARD) in India. Both NUBL and NABARD groups use self-regulation (peer selection, peer monitoring, and peer enforcement of contracts) as key to gaining access to services not otherwise available to them.... The NABARD experience is government-led. NUBL, on the other hand, was established as an alternative to government action. In both cases, government policy in the form of mandatory "priority sector" credit played --and continues to play --a critical role in facilitating expansion. The subsidy content (explicit and implicit) of both NUBL and the NABARD program is quite high, and continued expansion of both programs is highly conditional on whether the policy regime of directed credit continues. Any change in this policy will deal a severe blow to both of these institutions.